2005
DOI: 10.1091/mbc.e05-07-0642
|View full text |Cite
|
Sign up to set email alerts
|

Cdk1 and Okadaic Acid-sensitive Phosphatases Control Assembly of Nuclear Pore Complexes inDrosophilaEmbryos

Abstract: Disassembly and reassembly of the nuclear pore complexes (NPCs) is one of the major events during open mitosis in higher eukaryotes. However, how this process is controlled by the mitotic machinery is not clear. To investigate this we developed a novel in vivo model system based on syncytial Drosophila embryos. We microinjected different mitotic effectors into the embryonic cytoplasm and monitored the dynamics of disassembly/reassembly of NPCs in live embryos using fluorescently labeled wheat germ agglutinin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
57
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 54 publications
8
57
0
Order By: Relevance
“…The WGA-Nup persisted at the NE into late prometaphase, longer than Nup107. As reported previously (Onischenko et al, 2005), and in marked contrast to Nup107, the WGA-Nup became evenly distributed in the cytoplasm and showed no enrichment in the spindle area during metaphase and anaphase. In telophase, the first reappearance of both markers at the NE was nearly coincident, although mRFP-Nup107 reached its half-maximal intensity at the NE slightly earlier than the WGA-Nup ( Figure 5B).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…The WGA-Nup persisted at the NE into late prometaphase, longer than Nup107. As reported previously (Onischenko et al, 2005), and in marked contrast to Nup107, the WGA-Nup became evenly distributed in the cytoplasm and showed no enrichment in the spindle area during metaphase and anaphase. In telophase, the first reappearance of both markers at the NE was nearly coincident, although mRFP-Nup107 reached its half-maximal intensity at the NE slightly earlier than the WGA-Nup ( Figure 5B).…”
supporting
confidence: 84%
“…These various aspects of NE and NPC remodeling during mitosis need to be spatially and temporally coordinated with other cell cycle events. Key regulators that contribute to this spatio-temporal coordination are mitotic kinases and phosphatases as well as the small GTPase Ran and the transport receptors of the karyopherin/importin ␤ family (for reviews, see Dasso, 2002;Harel and Forbes, 2004;Hetzer et al, 2005;Margalit et al, 2005; see also Onischenko et al, 2005). In addition, there is growing evidence that NPCs functionally participate in mitosis.…”
Section: Introductionmentioning
confidence: 99%
“…We chose to focus on the nuclear envelope. Mitotic disassembly of the nuclear lamina and of the nuclear pore complex (NPC) are known to be imposed in large part by Cdk activity (33,34).…”
Section: Many Phosphorylation Sites Identified Lack An Optimal Cdk Comentioning
confidence: 99%
“…A recent study using temperature-sensitive Cdk1 Drosophila embryos showed that Cdk1 activity is required for keeping NPCs dissociated during mitosis, while the reassembly may be phosphatase-dependent (18). The goal of the present study is to map and characterize the cell-cycle-dependent phosphorylation of the main components of the Nup107-160 subcomplex to throw light on the regulation of disassembly and reassembly of the NPC.…”
mentioning
confidence: 95%